2020
DOI: 10.32607/actanaturae.11096
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profile as a marker of cell damage and immune dysfunction after spinal cord injury

Abstract: This study reviews the findings of recent experiments designed to investigate the cytokine profile after a spinal cord injury. The role played by key cytokines in eliciting the cellular response to trauma was assessed. The results of the specific immunopathogenetic interaction between the nervous and immune systems in the immediate and chronic post-traumatic periods are summarized. It was demonstrated that it is reasonable to use the step-by-step approach to the assessment of the cytokine profile after a spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…We found that the plasma levels of almost all cytokines were significantly upregulated following traumatic spinal cord injury. We focused on cytokine production during the early acute stage of the spinal cord injury [ 18 , 19 ], since on the second day following SCI, the release of cytokines by bone marrow cells decreases [ 20 ]. Importantly, groups of experimental animals with favorable and adverse outcomes, which initially were formed according to nonsubjective neurophysiologic treadmill test, demonstrated a dramatic difference in the severity of the plasma cytokine storm after 12 h following SCI.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the plasma levels of almost all cytokines were significantly upregulated following traumatic spinal cord injury. We focused on cytokine production during the early acute stage of the spinal cord injury [ 18 , 19 ], since on the second day following SCI, the release of cytokines by bone marrow cells decreases [ 20 ]. Importantly, groups of experimental animals with favorable and adverse outcomes, which initially were formed according to nonsubjective neurophysiologic treadmill test, demonstrated a dramatic difference in the severity of the plasma cytokine storm after 12 h following SCI.…”
Section: Discussionmentioning
confidence: 99%
“…This peptide, 17.1, and its truncated variant, 17.1a, have the potential to inhibit cytotoxic signal transmission through the TNFR1 receptor [ 23 ]. Recently, it has been shown that administration of peptide 17.1 to mice with the CFA-induced experimental arthritis has a protective effect against cartilage and bone destruction [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%